2017
DOI: 10.1186/s12884-017-1251-6
|View full text |Cite
|
Sign up to set email alerts
|

Duration of second stage of labor and instrumental delivery as risk factors for severe perineal lacerations: population-based study

Abstract: BackgroundWe sought to investigate the impact of the duration of second stage of labor on risk of severe perineal lacerations (third and fourth degree).MethodsThis population based cohort study was conducted in the Stockholm/Gotland region, Sweden, 2008–2014. Study population included 52 211 primiparous women undergoing vaginal delivery with cephalic presentation at term. Unconditional logistic regression analysis was used to calculate crude and adjusted odds ratios (OR), using 95% confidence intervals (CI). M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
1
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 27 publications
(33 reference statements)
6
71
1
8
Order By: Relevance
“…[9][10][11][12] Many studies showed multiparity as a protective factor against perineal tears and a higher incidence of intact perineum. [13][14][15] Women in this study were mainly in their first pregnancy; however, after the multiple analysis, the chance of spontaneous perineal tear decreased for each previous vaginal childbirth.…”
Section: Discussionmentioning
confidence: 75%
“…[9][10][11][12] Many studies showed multiparity as a protective factor against perineal tears and a higher incidence of intact perineum. [13][14][15] Women in this study were mainly in their first pregnancy; however, after the multiple analysis, the chance of spontaneous perineal tear decreased for each previous vaginal childbirth.…”
Section: Discussionmentioning
confidence: 75%
“…We observed that residents were more exposed to VEs during night shifts, but this did not influence the risk of OASIS. It was also more common for residents to handle VE after prolonged pushing, which may increase the risk of OASIS . However, the observed association between resident operators and OASIS actually increased after adjusting for this and other possible confounders.…”
Section: Discussionmentioning
confidence: 92%
“…Several studies have examined risk factors for OASIS in spontaneous and operative vaginal deliveries . Few studies have investigated operator‐related risk factors associated with OASIS in VE .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2. Summary of described risk factors for obstetric anal sphincter injuries (15,(21)(22)(23)(24)(25)(26)(27)(28). OASIS -obstetric anal sphincter injuries.…”
Section: Risk Factors For Third-degree Perineal Lacerationsmentioning
confidence: 99%